Emotional analysis of multiplayer online battle arena games addiction - Huang, Enwu; Xing, Yalong; Song, Xiaozhou (Frontiers in Psychology, 2024)
Introduction: Multiplayer Online Battle Arena (MOBA) games have garnered widespread popularity as a form of recreational activity. The launch of League of Legends (LoL), a prominent MOBA game, has captivated the enthusiastic pursuit of gamers in the MOBA community. The surge in MOBA game fervor, coupled with the influence of personal emotions, can result in excessive engagement, ultimately leading to addiction. Objective: This study aimed to investigate the moderating effects of visceral perception, behavior, and reflection on game players' addiction within the framework of Leisure Theory (LT), Uses and Gratification Theory (UGT), and Emotional Design Theory (EDT). Methods: A hypothesized theoretical model was developed and empirically evaluated based on 236 self-reported validated responses from MOBA gamers. SPSS (version 26) was employed for demographic analysis and game duration analysis. The measurement model and structural model analyses were conducted in two stages using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1.0 to validate the nine theoretical hypotheses. Results: It has been observed that personal emotions significantly contributes to MOBA game addiction during gamers' leisure time or moments of gratification. Specifically, a noteworthy connection exists between two dimensions, namely gamers' behavior and reflection, demonstrating a positive correlation with gaming addiction. Without taking entertainment as a motivating factor, there is no significant relationship between gamers' leisure-time and visceral perception.This study enhances the theoretical model of gamers' behavioral motives in engaging with MOBA gaming and contributes to the expansion of research on game addiction theory. These findings offer valuable theoretical insights for emotional design in games and the design of mechanisms for preventing game addiction.